Європейський досвід державного регулювання інноваційного розвитку агропромислового комплексу - Шпортюк, Наталія Леонідівна; Shportyuk, N. (ТОВ «ДКС - центр», 2019)
Україна, ставши на шлях незалежного розвитку, отримала надію на побудову стабільної, високорозвиненої країни та здійснила перетворення в економічному житті суспільства. Однією з важливих умов стабільності суспільства, що дає змогу ефективно функціонувати в умовах різних впливів, зберігаючи при цьому свою структуру і здатність контролювати процес суспільних змін, є економічна політика, важливим завданням якої є активна участь держави як атрибут соціально ефективної ринкової економіки. У даній статті відображені розробка та обґрунтування деяких напрямків державної підтримки агропромислового комплексу України для створення умов щодо формування конкурентоспроможних агропромислових підприємств. Так само, в статті описується вітчизняний і зарубіжний досвід державної підтримки досліджуваного сектора національної економіки. Статтю присвячено питанням інноваційного розвитку аграрного сектора економіки, гуртуючись на досвіді зарубіжних країн. Розглянуто причини зниження рівня активності інвестицій в інноваційні розробки АПК і методи державного стимулювання інноваційної діяльності в аграрній комплексі. - Agriculture is one of the main sectors of the economy of Ukraine. It is one of the few industries that consume products of practically all production and non-productive spheres of the Ukrainian economy. This is a strategically important branch, the status of which largely depends on the living standards of Ukraine and the food security of our country. For many years, the agrarian sector was not given enough attention from the government of our country. But in recent years, a dramatic change in the attitude towards agriculture has allowed to intensify processes of both vertical and horizontal integration: large integrated complexes, cooperative associations of small forms of agribusiness are created. They bear the main burden on the production of agricultural products. This article reflects the development and justification of some areas of state support for the agroindustrial complex of Ukraine to create conditions for the formation of competitive agro-industrial enterprises. Similarly, the article describes the domestic and foreign experience of state support to the investigated sector of the national economy. The article is devoted to issues of innovative development of the agrarian sector of the economy, grouping on the experience of foreign countries. The reasons for reducing the level of investment activity in innovation development of agro-industrial complex and methods of state stimulation of innovation activity in agrarian complex are considered. At the current stage, the European Union has well-functioning rural development programs. Many rural development programs are fully in line with the goals of the development of rural areas of Ukraine, such as support for small and medium-sized businesses, support for the production of environmentally friendly products, the development of programs that promote the interest of young people in agricultural activities, the widespread introduction of innovations in the agricultural sector of the economy. Therefore, studying the EU experience on rural development, in our opinion, will help to develop optimal solutions for solving the problem issues of Ukrainian rural areas and their more effective development.
European experience of state regulation of innovative development of agro-industrial complex
Keywords: державна політика; state policy; регулювання; regulation; європейський досвід; European experience; економічна політика; economic policy